Optimalisasi Kapasitas Rooftop PV System Skala Rumah Tangga di Perumahan - Fadhillah Hazrina; Betti Widianingsih; Riyani Prima Dewi (P3M Politeknik Negeri Cilacap, 2022)
One of the renewable energies in Indonesia is solar energy. The geographical condition of Indonesia, which is a tropical country, is one of the advantages it has for applying solar energy. The Indonesian government is gradually regulating the population system for Solar Power Plants (PLTS). The resident system is in demand because of the advantage that it can be connected to the PLN grid and used as an energy reserve. The installation of rooftop PLTS both in government buildings and on the roofs of houses has now become a common trend in the community as a form of participation in the use of New and Renewable Energy (EBT). Before installing PLTS Roofs, it is necessary to determine in advance how much capacity will be installed. This is also related to the community's question, what is the percentage of electricity costs if PLTS roofs are installed in bulk. These designs and calculations are generally carried out with the help of simulations. To discuss these problems, in this article, we will discuss a simulation of the potential for electrical energy generated from rooftop solar power plants in Cilacap Green Smart Living housing. The simulation was carried out with the help of the SolarGIS PV lunar device. Analytical calculations are carried out by software based on input of regional location and solar irradiation. SolarGis will calculate the daily output power generated by the rooftop PV mini-grid and the average monthly and yearly power. The simulation results show that one house with a daily energy requirement of 13 kWh by installing a rooftop PLTS with a capacity of 3 kWp, the demand for electrical energy imported from the PLN network to the house is only 7.8% in one year.